Pengembangan Aplikasi Game Edukatif Wordwall pada Materi Penjajahan Belanda di Palembang Kelas XI SMK PGRI Tanjung Raja - Winata, Oktami; Pahlevi, Muhammad Reza (Riwayat: Educational Journal of History and Humanities, 2025)
This research aims to develop historical learning media in the form of Wordwall educational games on the material of Dutch Colonization in Palembang for class XI SMK PGRI Tanjung Raja. The research method uses the Alessi and Trollip development model which includes planning, design, and development stages. Validation was carried out by media experts and material experts with very valid results, namely 93.05% and 91.66%. The product was also tested on educators and 53 students from two classes, which resulted in a very good response with an average of 99.60%. These results show that the learning media developed is feasible to use and able to increase students' interest and involvement in learning history.